Phylogeography and conservation genetics of the Amazonian freshwater stingray Paratrygon aiereba Müller & Henle, 1841 (Chondrichthyes: Potamotrygonidae) - Frederico, Renata Guimarães (2012)
The family Potamotrygonidae is monophyletic comprising three genera: Paratrygon Duméril, Potamotrygon Garman and Plesiotrygon Rosa, Castello & Thorson. The distribution of most species in this family is restricted to a single basin or fluvial system. Only Potamotrygon motoro, Potamotrygon orbignyi and Paratrygon aiereba are found in more than one river basin. In this study we investigate genetic structuring of Paratrygon aiereba, from five rivers of the Amazon region: Negro, Solimões- Amazon-Estuary system, Tapajós, Xingu and Araguaia. Sixty-three individuals were sequenced for ATPase 6, and a representative subsample of 27 individuals was sequenced for COI. The COI dataset analysis indicated that Paratrygon is sister to all other potamotrygonid genera and species. Population parameters inferred from the analysis of ATPase 6 sequences revealed that the populations of this species are structured within each river, with no or nearly non-existent gene flow occurring between rivers and a positive correlation between geographic and genetic distances. Paratrygon aiereba is comprised of three geographically restricted clades with K2P interclade distances of at least 2%. Intraspecific divergence within P. aiereba is similar to the interspecific divergence observed in Potamotrygon spp. sampled throughout the same geographic area. Using the premises of COI barcoding and the allopatric distribution of the three P. aiereba clades, the taxon P. aiereba most likely comprises three distinct biological species. Since freshwater stingrays of the family Potamotrygonidae are highly exploited for the aquarium trade, management and conservation strategies need to be implemented at the level of each river basin, rather than at the level of the Amazon basin. © 2012 Sociedade Brasileira de Ictiologia.